2010
DOI: 10.1038/oby.2010.97
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Magnetic Resonance Fat Measurements in Humans Correlate With Established Methods but Are Biased

Abstract: Precision and accuracy of the quantitative magnetic resonance (QMR) system for measuring fat in phantoms and total body fat (TBF) in humans were investigated. Measurements were made using phantoms: oil, beef with water, beef with oil, and humans with oil and water. TBFQMR in humans was compared with TBF by a four-compartment model (TBF4C). The coefficient of variation (CV) for replicate TBFQMR was 0.437%. QMR fat was lower at 23 °C vs. 37 °C. The fat increase in QMR phantom studies was consistent with the oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 15 publications
(24 reference statements)
4
58
1
1
Order By: Relevance
“…8,[17][18][19][20] However, several studies also showed that QMR underestimated FM when using deuterium dilution and a fourcomponent model as the gold standard. [21][22][23][24][25][26] Values for both FM and FFM, while significantly different from CCA values, were still significantly correlated for each body compartment measure. For FFM, residual bias increased significantly with increasing CCA mass, while residual bias did not occur for FM.…”
Section: Discussionmentioning
confidence: 81%
“…8,[17][18][19][20] However, several studies also showed that QMR underestimated FM when using deuterium dilution and a fourcomponent model as the gold standard. [21][22][23][24][25][26] Values for both FM and FFM, while significantly different from CCA values, were still significantly correlated for each body compartment measure. For FFM, residual bias increased significantly with increasing CCA mass, while residual bias did not occur for FM.…”
Section: Discussionmentioning
confidence: 81%
“…The FM underestimation by QMR in obese women is in accordance with a previous report. 6 Combining normal weight and obese women into one group neutralized the differences in the present study, and resulted in very accurate average FM estimates by QMR, although the common BlandeAltman plot showed that FM errors were systematic. Hence, QMR could possibly be appropriate for large heterogeneous populations.…”
Section: Quantitative Magnetic Resonancementioning
confidence: 76%
“…The nuclear magnetic resonance signals from fat, free water and muscle mass differ, 8 and multiple linear regression prediction formulas calibrated against canola oil, lean animal tissues and tap water are used to calculate fat, lean mass and free water. 6 Total body water is then derived from the difference between the total amount of protons and the fat found by regression analysis. 8 Consequently, TBW by QMR includes the sum of free water and water in lean mass.…”
Section: Quantitative Magnetic Resonancementioning
confidence: 99%
See 2 more Smart Citations